Feasibility, safety, and efficacy of endovascular treatment of anterior cranial fossa dural arteriovenous fistulas: a systematic review and meta-analysis with a subanalysis for Onyx - Ferreira, Marcio Yuri; Gunkan, Ahmet; Batista, Savio; Porto, Mauricio; Camerotte, Raphael; de Barros Oliveira, Leonardo; Porto Junior, Silvio; Okoye, Obiora; da Fonseca, Igor Oliveira [UNESP]; Bertani, Raphael; Tanus Machado, Elias Antonio; Ferreira, Christian; et al. (Springer Nature, 2024)
Dural Arteriovenous Fistulas (dAVFs) of the anterior cranial fossa (ACF) are uncommon but carry a high risk of hemorrhage and pose substantial treatment challenges. Recent advancements in endovascular treatment (EVT), including the introduction of novel liquid embolic agents, have markedly bolstered EVT’s role in managing ACF-dAVFs, with notable series published in the last five years. We aimed to assess the feasibility, safety, and efficacy of EVT for ACF-dAVFs. We searched Medline, Scopus, Web of Science, and Cochrane Library databases following PRISMA guidelines. Eligible studies included those with ≥ 5 patients undergoing embolization of ACF-dAVFs, detailing both angiographic and clinical outcomes. We used single proportion analysis with 95% confidence intervals under a random-effects model, I2 to assess heterogeneity, and Baujat and sensitivity analysis to address high heterogeneity. Publication bias was assessed by funnel-plot analysis and Egger’s test. Outcomes included complete occlusion following embolization, unsuccessful endovascular embolization attempts, incomplete occlusion following embolization, symptom resolution or clinical improvement following embolization, recurrence; procedure-related complications, morbidity, and mortality. Additionally, a subanalysis for studies exclusively utilizing Onyx™ embolic system was done. Eighteen studies comprising 231 ACF-dAVF were included. Unsuccessful endovascular embolization attempts rate was 2%. Complete occlusion rate was 85%, with 4% of complications. Incomplete occlusion rate was 10%. Successfully embolized patients experienced either symptom resolution or clinical improvement in 94% of cases. Morbidity and mortality rates were 1% and 0%, respectively. Onyx subanalyses showed an overall rate of 0% for unsuccessful attempts, 95% for complete occlusion, and 5% for incomplete occlusion. Symptom resolution or clinical improvement was 98% and recurrence rate was 0%. EVT for ACF-dAVF is highly feasible, effective, and safe, with a low rate of complications, morbidity, and mortality. The subanalyses focusing on Onyx embolizations revealed superior efficacy and safety outcomes compared to the findings of the primary analyses involving all included studies.
Keywords: Anterior cranial fossa; Dural arteriovenous fistula; Embolization; Endovascular; Ethmoidal; Onyx